2008
DOI: 10.1038/nature06933
|View full text |Cite
|
Sign up to set email alerts
|

Multi-genetic events collaboratively contribute to Pten-null leukaemia stem-cell formation

Abstract: Cancer stem cells, which share many common properties and regulatory machineries with normal stem cells, have recently been proposed to be responsible for tumorigenesis and to contribute to cancer resistance 1 . The main challenges in cancer biology are to identify cancer stem cells and to define the molecular events required for transforming normal cells to cancer stem cells. Here we show that Pten deletion in mouse haematopoietic stem cells leads to a myeloproliferative disorder, followed by acute T-lymphobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
261
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(284 citation statements)
references
References 27 publications
(28 reference statements)
19
261
0
1
Order By: Relevance
“…Of the cancers that developed in PTEN þ /À mice, 88% were classified as T-ALL (Suzuki et al, 1998). Furthermore, mice reconstituted with PTEN À/À hematopoietic stem cells (HSCs) developed T-ALL that harbored translocations resulting in aberrant expression of c-myc (Guo et al, 2008). Interestingly, no activating Notch mutations were found in these tumors, however, the phenotype was the same as those tumors induced by N ICD (CD4 þ CD8 þ ), suggesting that PTEN inactivation can compensate for some Notch-mediated processes in T-ALL, namely, suppression of p53-mediated apoptosis (Figure 4).…”
Section: Notch Suppresses P53 In T-allmentioning
confidence: 99%
“…Of the cancers that developed in PTEN þ /À mice, 88% were classified as T-ALL (Suzuki et al, 1998). Furthermore, mice reconstituted with PTEN À/À hematopoietic stem cells (HSCs) developed T-ALL that harbored translocations resulting in aberrant expression of c-myc (Guo et al, 2008). Interestingly, no activating Notch mutations were found in these tumors, however, the phenotype was the same as those tumors induced by N ICD (CD4 þ CD8 þ ), suggesting that PTEN inactivation can compensate for some Notch-mediated processes in T-ALL, namely, suppression of p53-mediated apoptosis (Figure 4).…”
Section: Notch Suppresses P53 In T-allmentioning
confidence: 99%
“…12,13 There is a strong rationale for targeting PI3K/Akt/mTOR signals in T-ALL, as in mice hematopoietic stem cells, PTEN deletion (which results in PI3K/Akt/mTOR hyperactivation) led to a T-ALL. 14,15 Moreover, recent findings in a zebrafish model, have highlighted that the transition from T-lymphoblastic lymphoma to T-ALL was characterized by increased phosphorylation levels of Akt. 16 The allosteric inhibition of mTORC1 by rapamycin has only modest effects on T-ALL cells.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the molecular and cellular mechanisms associated with PTEN-controlled T-ALL pathogenesis and therapeutic resistance, we have recently developed a Pten loxP/loxP ;VE-CadherinCre + ;Rosa26 loxP-stop-loxP -LacZ + (Pten null) T-ALL mouse model by conditional deletion of Pten in a subset of fetal liver hematopoietic stem cells (8). The resulting animals develop a transient myeloproliferative disorder followed by T-ALL with 100% penetrance.…”
mentioning
confidence: 99%
“…The resulting animals develop a transient myeloproliferative disorder followed by T-ALL with 100% penetrance. Besides Pten deletion, at least two subsequent spontaneous alterations, namely β-catenin activation and a Tcrα/δ-c-myc translocation, have been identified, which lead to the transformation of T-progenitor cells to self-renewable leukemia stem cells (LSCs) enriched in the c-Kit mid CD3 + Lin − subpopulation (8). Our previous work showed that this LSC subpopulation is responsible for initiating T-ALL and repopulating and maintaining leukemia development in SCID recipients on serial transplantation (8).…”
mentioning
confidence: 99%